An Efficient Derivative-Free Method for the Solution of Systems of Equations. (1st July 2021) - Chun, Changbum; Neta, Beny
Abstract: We have modified our previously developed fourth order method to approximate solution of systems of equations including non-differentiable ones. The most recent article by Kumar et al. (Numer. Algor. 86:1051–1070, 2021) compared fourth order and seventh order methods to show the efficiency of their fourth order. We have shown that our method compares favorably with methods in the literature.